Central limit theorem for special classes of functions of ergodic chains - Moskal'tsova, N. V.; Shurenkov, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
A central limit theorem is proved for E-finite bounded functions of ergodic Markov chains. Two useful corollaries are presented.